Pengembangan media pembelajaran m-learning berbasis android pada mata pelajaran PPKn materi lembaga-lembaga negara kelas X - Andiansyah Bagus Rahmadila; Rosyid Al Atok; Rista Ayu Mawarti (Universitas Negeri Malang, 2022)
This paper discusses about the development of android-based mobile learning media for the teaching of Civics subject at SMAN 1 Purwosari. This study aims at producing an android-based learning media on Civics subject, particularly about The State Institutions material. This development research uses the ADDIE model which consists of five steps, namely: analysis, design, development, implementation, and evaluation. The feasibility of the media was validated by media expert, material expert, linguist, and practitioner. After the validation stage, a limited trial was conducted to the 10th grade students of SMAN 1 Purwosari. The results of the media feasibility validation and limited trial are as the following: (1) the media expert scored 3,97 with